Sexual Dimorphisms of Preeclampsia-Dysregulated Transcriptomic Profiles and Cell Function in Fetal Endothelial Cells. Issue 1 (July 2019) - Zhou, Chi; Yan, Qin; Zou, Qing-Yun; Zhong, Xin-Qi; Tyler, Chanel T.; Magness, Ronald R.; Bird, Ian M.; Zheng, Jing
Abstract : Preeclampsia impairs fetoplacental vascular function and increases risks of adult-onset cardiovascular disorders in children born to preeclamptic mothers, implicating that preeclampsia programs fetal vasculature in utero. However, the underlying mechanisms remain elusive. We hypothesize that preeclampsia alters fetal endothelial gene expression and disturbs cytokines- and growth factors-induced endothelial responses. RNA sequencing analysis was performed on unpassaged human umbilical vein endothelial cells (HUVECs) from normotensive and preeclamptic pregnancies. Functional assays for endothelial monolayer integrity, proliferation, and migration were conducted on passage 1 HUVECs from normotensive and preeclamptic pregnancies. Compared with normotensive cells, 926 and 172 genes were dysregulated in unpassaged female and male HUVECs from preeclamptic pregnancies, respectively. Many of these preeclampsia-dysregulated genes are associated with cardiovascular diseases (eg, heart failure) and endothelial function (eg, cell migration, calcium signaling, and endothelial nitric oxide synthase signaling). TNF (tumor necrosis factor)-α–, TGF (transforming growth factor)-β1–, FGF (fibroblast growth factor)-2–, and VEGFA (vascular endothelial growth factor A)–regulated gene networks were differentially disrupted in unpassaged female and male HUVECs from preeclamptic pregnancies. Moreover, preeclampsia decreased endothelial monolayer integrity in responses to TNF-α in both female and male HUVECs. Preeclampsia decreased TGF-β1–strengthened monolayer integrity in female HUVECs, whereas it enhanced FGF-2–strengthened monolayer integrity in male HUVECs. Preeclampsia promoted TNF-α–, TGF-β1–, and VEGFA–induced cell proliferation in female, but not in male HUVECs. Preeclampsia inhibited TNF-α–induced cell migration in female HUVECs, but had an opposite effect on male HUVECs. In conclusion, preeclampsia differentially dysregulates cardiovascular diseases- and endothelial function-associated genes/pathways in female and male fetal endothelial cells in association with the sexual dimorphisms of preeclampsia-dysregulated fetal endothelial function. Abstract : Supplemental Digital Content is available in the text.